(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Kerala has made significant contribution to Ayurvedic literature. The traditional medical knowledge, gained from years of critical observations and clinical experiences has been documented by the great physicians. The medical literature of Kerala can be classified as, commentaries of the original texts as well as independent works based on these texts, compilation works by details of Oushada yogas and Kriyakramas from the Vaidyas. The text book of regional literature are rich source of information’s like formulations and treatment modalities based on geographical, climatic and cultural situations of various regions, based on their thoughts and lifestyle. The text Arogya chandrika athava kudumba vaidyan written by Sri Swami Sachidananda is an important work both from medical and poetic merits. The book was written in Malayalam language because it is specially meant for the native physicians of Kerala. It is a user– friendly text for the guidance of students and physicians. The uniqueness of the text is that it has mentioned simple and potential treatments for common diseases. The text is enriched with grammatical styles like Vritha. The text addresses the preventive as well as curative concept of Ayurvedic thoughts. Arogya chandrika athava kudumba vaidyan can be considered as an important contribution from Kerala’s regional literature to the Ayurveda community. The present paper is to critically analyze the subject matter of the text Arogya chandrika athava kudumba vaidyan. This will definitely enrich the literary data base of Ayurveda.